2005
DOI: 10.1592/phco.2005.25.12.1752
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-Related Health Care Resource Use Among Patients Starting Fluticasone or Montelukast Therapy

Abstract: The start of therapy with either fluticasone or montelukast as a single-controller for asthma was associated with similar asthma-related health care resource use in this matched population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Among the monotherapy groups, the LM group appeared to have better clinical outcomes than the ICS group, as indicated by less SABA use and lower risk of INP/ED visits. This finding was in line with those of some previous studies 12,26 ; however, it conflicted with the 2002 and 2007 NAEPP guidelines, which recommended ICS as the preferred monotherapy. 4,27 This conflict could be due to the observation that the patients in this study were less adherent to an inhaled controller medication (ICS, LABA) regimen than to an oral controller medication (LM) regimen.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Among the monotherapy groups, the LM group appeared to have better clinical outcomes than the ICS group, as indicated by less SABA use and lower risk of INP/ED visits. This finding was in line with those of some previous studies 12,26 ; however, it conflicted with the 2002 and 2007 NAEPP guidelines, which recommended ICS as the preferred monotherapy. 4,27 This conflict could be due to the observation that the patients in this study were less adherent to an inhaled controller medication (ICS, LABA) regimen than to an oral controller medication (LM) regimen.…”
Section: Discussionsupporting
confidence: 90%
“…findings of some other studies, 12,34 the real reasons for this trend remain unknown and require further study. The importance of this finding is reduced by the fact that this study found no differences in patient-reported measures of asthma control between the ICS monotherapy group and the LM monotherapy group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…13,[15][16][17][18][19][20][21][22] The total cost/patient/year of $3745 in the present study is similar to the cost of $3180 found in an earlier smaller cross-sectional study of randomly sampled Northern California adults with asthma. 23 The total cost savings/patient/year reported here of $749 with single controller ICS versus single controller LM compares well to the differential cost between these drugs of $1080 reported in a meta-analysis of 6 smaller MCO claim studies 11 and of $1197 found in a study of 2.6 million privately insured individuals.…”
Section: Discussionsupporting
confidence: 81%
“…Most prior reports comparing LTRAs and ICS are retrospective database studies of healthcare resource use and costs in the US. [37][38][39][40][41][42][43][44] While some of these studies described similar asthmarelated resource use and costs for patients using these two drug classes, [38,40,41,43] the weight of the evidence from these studies supports better cost effectiveness of ICS, in part because of lower acquisition costs relative to LTRAs. [37,38,43] Prior studies did not examine indirect costs.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%